Pengaruh Digital Marketing Dan Brand Awareness Terhadap Minat Beli Produk Subeng Klasik - Mareta Nurul Fitri; Siti Mabrur Rachmah (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study is to analyze the influence of digital marketing on consumer interest in buying